2017
DOI: 10.1371/journal.pone.0168368
|View full text |Cite
|
Sign up to set email alerts
|

Age Related Patterns of Disease and Mortality in Hospitalised Adults in Malawi

Abstract: BackgroundThe epidemic of non-communicable diseases (NCDs) in low and middle income countries (LMICs) is widely recognised as the next major challenge to global health. However, in many LMICs, infectious diseases are still prevalent resulting in a “double burden” of disease. With increased life expectancy and longevity with HIV, older adults may particularly be at risk of this double burden. Here we describe the relative contributions of infections and NCDs to hospital admissions and mortality, according to ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 18 publications
5
27
1
Order By: Relevance
“…Tuberculosis continues to be the leading presumed cause of morbidity and mortality among HIV‐positive patients. Our results are consistent with findings from other settings in sub‐Saharan Africa demonstrating ongoing high rates of HIV‐positive admissions and associated mortality (especially from tuberculosis) despite increased availability of ART , and contrast with experience from Europe and North America where HIV has become a condition largely managed in the outpatient setting . These differences are likely explained by health system resources, differences in tuberculosis prevalence, different spectrum of opportunistic infections and socio‐economic factors which disadvantage patients in developing‐country settings.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Tuberculosis continues to be the leading presumed cause of morbidity and mortality among HIV‐positive patients. Our results are consistent with findings from other settings in sub‐Saharan Africa demonstrating ongoing high rates of HIV‐positive admissions and associated mortality (especially from tuberculosis) despite increased availability of ART , and contrast with experience from Europe and North America where HIV has become a condition largely managed in the outpatient setting . These differences are likely explained by health system resources, differences in tuberculosis prevalence, different spectrum of opportunistic infections and socio‐economic factors which disadvantage patients in developing‐country settings.…”
Section: Discussionsupporting
confidence: 88%
“…Few ART‐era studies from the African region have previously reported on rates of ART‐coverage and mortality among HIV‐positive adult medical admissions. The HIV‐related medical inpatient mortality rate of 22% on our wards was similar to that from hospital settings in Malawi (24%, 25%) where a comparable ART‐coverage rate (72%) was reported and lower compared to a multi‐centre study from West Africa which reported 38% mortality in the setting of lower (48%) ART‐coverage . Widely divergent HIV‐related inpatient mortality rates of 17% and 30% have been reported from settings in Kenya and DRC respectively, where a relatively high proportion of patients were on ART at the time of admission .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“… 5 NCDs are considered among the leading causes of death, second only to HIV/AIDS, 6 and a recent study on inpatients in Malawi found that, while infections remain the leading cause of adult admission, NCDs were the most frequent causes of death in adults over 55 years old. 7 The high burden of NCDs in Africa presents challenges to providing NCD care, as these countries also have a huge burden of communicable diseases, notably HIV/AIDS and its complications.…”
Section: Introductionmentioning
confidence: 99%
“…Already in Malawi new studies are emerging that should give us a better picture (though by no means a comprehensive one) of the actual incidence of noncommunicable disease, beyond but including those framed within the terms of 'metabolic disorders' (Price et al in preparation). These studies will also be able to link non-communicable disease to infectious disease, particularly HIV/AIDS and its chemotherapy, as well as to economic status, education and levels of urbanisation, a range of environmental effects and ageing (for example, Allain et al 2017;Moses et al 2017). Moving away from 'transition' to a more complex conceptualisation of the temporalities of epidemiological change also has the potential to give us a somewhat different understanding of what may indeed a creeping 'epidemic' of type 2 diabetes and other conditions.…”
Section: Resultsmentioning
confidence: 99%